PENGARUH MOTIVASI KERJA TERHADAP KOMITMEN ORGANISASI KARYAWAN (Studi pada Karyawan PT Transito Adiman Jati) - Angella Frederica; Kaduci Kaduci; Riza Hadikusuma (SEMNASTERA (Seminar Nasional Teknologi dan Riset Terapan), 2020)
Angella Frederica. The Influence of Work Motivation on Organizational Commitment (Study on Employees of PT Transito Adiman Jati). Business Administration, State Polytechnic of Jakarta. 2020.This study is based on employee responses who are less alert to customer requests. The purpose of this research is to find out the influence of work motivation on organizational commitment in PT Transito Adiman Jati. The methodology used in this research is quantitative methods with 26 person samples. The research data were processed using SPSS software 26.0 version for windows. The regression equation in this research is Y=6,739+0,557x. Through calculation with simple correlation valued 0,739, it indicates that work motivation and organizational commitment had strong ties. Based on analysis of determined coefficients, obtained the percentage of 54.7 % while the rest 45,3 % influenced by other variables that not be researched, such as: work satisfaction, stress, motivation, trust, justice, and learning and decision-making.